Fragmentation of nanoplastics driven by plant-microbe rhizosphere interaction during abiotic stress combination - Yoon, Hakwon; Kim, Juntae; Chang, Yoon-Seok; Kim, Eun-Ju (Royal Society of Chemistry, 2021)
Large amounts of micro- and nanoplastics, which are released into the environment through environmental weathering of plastic items or sludge disposal/application, can end up in soil, being considered as a new plant abiotic stressor. In nature, plants face a number of abiotic stresses simultaneously. However, it is largely unknown whether and how abiotic stress combination affects the plant uptake of nanoplastics, and how plants tune the rhizosphere interactions to acclimate to a combination of nanoplastic and another abiotic stress. Here we show that smaller, fragmented nanoplastics can accumulate in the root of Arabidopsis thaliana under combined nanoplastic and Cd stresses. The specific changes in root exudation of organic acids and bacterial community composition that reveals a metabolic preference for aromatic compounds drive the degradation of nanoplastics in the rhizosphere. Our findings provide critical implications relevant to food security that nanoplastics will contaminate crops as well, and in turn, transfer along the human food chain.